Enhancing photoelectrochemical CO2 reduction: The impact of polyelectrolytes modification on copper oxide catalysts - Nabila Nawaz; Krzysztof Bienkowski; Karthick Ramalingam; Aleksandra Parzuch; Piotr Wróbel; Marcin Strawski; Renata Solarska (Journal of CO2 Utilization, 2025)
Reducing CO2 into value-added chemicals and fuels by artificial photosynthesis is a critical turnover in research as one of the considerable solutions to global environmental and energy issues. Copper (I) oxide (Cu2O), a low-cost semiconductor, is one of the promising candidates for application in CO2RR systems. However, the performance is still unsatisfactory, and the products, like acids and alcohols, can be obtained regarding the system parameters. Cu2O's main drawback is its susceptibility to photo corrosion, which limits its effectiveness in the CO2 reduction reaction (CO2RR) due to instability. The presence of Cu+ on the electrode surface is essential for suppressing hydrogen evolution and improving CO2RR selectivity. In this study, we explore the use of polyethyleneimine (PEI) to enhance the performance of Cu2O electrodes and protect against photo corrosion. We hypothesized that PEI's amine groups would bind CO2 and facilitate its transformation into intermediate products during reduction reactions. Chronoamperometry and mass spectrometry results showed that, after 20 h, the photostability of PEI-coated electrodes was significantly improved compared to bare Cu2O. Under illumination at 0.3 V vs. RHE, the PEI@Cu2O photocathode produces methanol, ethanol, and formate species. Our preliminary findings suggest that PEI might be an effective tool for CO2 capture and utilization.